Foreign Language Lessons as a Method of Developing Confident and Worthy Behavior of Students - Trudnikova, Darya Dmitrievna; Sorokoumova, Galina Veniaminovna (Razvitie obrazovaniâ (Online), 2020)
The authors of the article emphasize that modern realities require the development of skills of confident and worthy behavior in all situations, etc. It is noted that skills must be developed in learning process using various methods and techniques in the classroom and off-hour work using various psychological trainings to create a psychologically safe and comfortable educational environment. The study of the impact of applying personal-oriented teaching methods in English language learning process on the formation of self-confidence, improving academic performance and increasing interest in a foreign language is described in the article. The purpose, hypothesis, tasks, methodological and theoretical basis of the research, methods and experimental base of the research are defined in the article; the results of the research of the summative, formative and control stages are analyzed. The method of Yakubovskaya P. was chosen as a diagnostic method at the summative and control stages of the study. P. Yakubovskaya's assessment test is aimed at the ability to distinguish between confident, insecure and aggressive behavior of an individual. The summative stage of the study showed that the majority of students do not see the line between confident and insecure behavior of the individual in situations that were taken as examples. It is mentioned that some guys couldn't tell the difference between confident and aggressive behavior. At the formative stage of the study, students in the control group studied using the classical method. For students of the experimental group, English lessons were developed and tested using specially designed tasks of a personality-oriented nature. During the control stage of the study, students who were part of the experimental group showed a significant increase in correct answers while doing the test. As a result of the analysis, it was found that the use of personality-oriented approach in the educational process positively affects the formation of self-confidence, improving academic performance and increasing interest in a foreign language in general, as well as contributing to the formation of a strong and self-confident personality.